Academic self-efficacy, grit, and teacher support as predictors of psychological well-being of Chinese EFL students - Tang, Lin; Zhu, Xiaojing (Frontiers in Psychology, 2024)
This study explores the determinants of psychological well-being among 968 Chinese English as a Foreign Language (EFL) students by employing Structural Equation Modeling (SEM). Focusing on academic self-efficacy, grit, and teacher support, this research aims to illuminate their roles in shaping the psychological well-being of EFL students within the Chinese educational context. Method: Data from a robust sample of Chinese EFL students were analyzed using SEM techniques to investigate the relationships between academic self-efficacy, grit, teacher support, and psychological well-being. Validated instruments were utilized to measure these constructs, ensuring accuracy and reliability. The study employed meticulous data collection procedures over a three-month period, maintaining strict ethical standards and anonymity for participants.The SEM analysis revealed intricate connections among academic self-efficacy, grit, teacher support, and the psychological well-being of Chinese EFL students. Academic selfefficacy and grit emerged as direct predictors of psychological well-being, highlighting their significance in fostering students' overall well-being. Additionally, teacher support was identified to play a mediating role in this relationship, emphasizing its critical influence on enhancing academic self-efficacy and grit, thereby contributing to students' psychological well-being. Discussion: These findings underscore the crucial importance of nurturing academic self-efficacy and grit to enhance the psychological well-being of Chinese EFL students. Furthermore, teacher support stands out as a pivotal factor in elevating students' academic self-efficacy and grit, emphasizing the need for educational interventions centered on fostering these attributes among Chinese EFL learners. The implications of these results extend to educational practices, emphasizing the indispensable role of teacher support and interventions aimed at cultivating academic self-efficacy and grit to promote the psychological well-being of EFL students within the learning environment.